PENINGKATAN AKTIVITAS DAN HASIL BELAJAR FISIKA MELALUI PEMBELAJARAN FISIKA GASING PADA SISWA KELAS X-2 SMA NEGERI 1 PINANGSORI TAHUN PELAJARAN 2016/2017 - Muhammad Ali (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2018)
This research is classroom action research aims to find out whether the study of physics gasing can improve student activity and learning outcomes. This research consists of 2 cycles conducted in X-2 class SMA Negeri 1 PinangsoriKabupatenTapanuli Tengah which amounted to 33 students. Characteristics of this class have low activity and learning outcomes compared to other X classes. The indicator of success for students at least 75%, and indicators of learning outcomes at least 85% of the number of students who take the test. During the study showed an increase in activity and student learning outcomes from cycle I to cycle II. In the first cycle students psychomotor average score at the end of the first cycle of 75.85 to 79.26 at the end of cycle II, the affective value of scientific attitude in the first cycle with an average of 78.03 and rose to 80.74 in cycle II. Student cognitive learning analysis is obtained through the results of the test per cycle conducted every cycle. Increased cognitive learning outcomes seen from the average value obtained by students before the cycle 65 with completeness 31%, at the end of the cycle I an average of 73.52 with 63.64% completeness and at the end of the second cycle to 78.18 with a complete 87.88 %. From the results of the research, it can be concluded that the application of learning physics gasing can increase the activity and the results of physics learning in students of class X-2 SMA Negeri 1 Pinangsori. Keywords: Activity, Learning Outcomes and Physics Gasing